Outlining a new collaborative business model as a result of the green Building Information Modelling impact in the AEC supply chain - Vilas-Boas, J.; Mirnoori, V.; Razy, A.; Silva, A. (Collaborative Networks and Digital Transformation, 2019)
BIM (Building Information Modelling) technological push has enabled to integrate the design/construction outcomes of 3D-CAD along the product/service AEC (Architecture, Engineering and Construction) SC (supply chain) through an intelligent DMS (Data Management System) based on standard and interoperable data formats. The proposed end-to-end approach overcomes a typical AEC gap, enables the operationalisation of the sustainable/green building LCA (Life Cycle Assessment) and puts together new collaborative relationships with the owner, among SC stakeholders and with new forms of BIM procurement. The outlined collaborative business model is based on the Quality Control and Assurance framework and provides conceptual consistency to the reintroduction of the owner concerns/satisfaction in the SC, as well as enables consistent and accountable relationships between (smart)materials procurement and building specification. An expert’s focus group carried out a preliminary check of the model’s interest/applicability, resulting in recommendations for its further detailing and for propositions development into a systematic enquiring process.